1956
DOI: 10.1083/jcb.2.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Dna in Gametogenesis and Embryogeny in Tradescantia

Abstract: Within recent years evidence has come from several lines of research that the gene is either composed of, or is at least intimately associated with, desoxyribose nucleic acid (DNA). Experiments in microbial genetics have shown that only the DNA fraction of the bacterial protoplast is capable of transforming other bacteria to the genetic type from which the DNA was originally derived (2). Further, both chemical extraction and photometric studies have supported the view that within a plant or animal the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1958
1958
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Other than the ci rrent investigation of G. gnemon, few studies of seed plants have documented nuclear DNA levels of gametes as well as zygotes (Woodard, 1956;Bennett and Smith, 1976;Friedman, 1991;Mogensen and Holm, 1995;. One of the first, and perhaps most compelling, studies on the relationship between the cell cycle and sexual reproduction was by Woodard (1956).…”
Section: Reproduction Among Seed Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other than the ci rrent investigation of G. gnemon, few studies of seed plants have documented nuclear DNA levels of gametes as well as zygotes (Woodard, 1956;Bennett and Smith, 1976;Friedman, 1991;Mogensen and Holm, 1995;. One of the first, and perhaps most compelling, studies on the relationship between the cell cycle and sexual reproduction was by Woodard (1956).…”
Section: Reproduction Among Seed Plantsmentioning
confidence: 99%
“…One of the first, and perhaps most compelling, studies on the relationship between the cell cycle and sexual reproduction was by Woodard (1956). Based on microspectrophotometry of Feulgen-stained nuclei in Tradescantia paludosa, Woodard (1956) found that egg cell nuclei contain the 1C quantity of DNA through fertilization, and newly formed zygotes contain the 2C amount. Sperm nuclei were not measurable but were inferred to contain the 1C quantity of DNA.…”
Section: Reproduction Among Seed Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear class or "C" value for each cell type in Tables I to IV are those reported for DNA content of nuclei of Tradescantia from several laboratories (42,52,59). In Tables V and VI DNA amounts were estimated directly by the usual photometric techniques (54) applied to Feulgen-stained sections adjacent to those on which histone determinations were made.…”
Section: Methodsmentioning
confidence: 99%